Analisis Pengaruh Perceived Harga, Kemasan dan Daya Tarik Iklan Televisi Terhadap Minat Beli Konsumen Produk Rokok Djarum Super di Bumiayu - Nisau Sopwa; Qori Al Banin (JBIMA (Jurnal Bisnis dan Manajemen), 2015)
This study is a survey research, which aim to investigate the influence of perceived price, packaging, and the attractiveness of television advertisement, to consumer buying interest of Djarum Super cigarette in Bumiayu. In this study, the data were collected by spreading questioners to the 100 consumers of Djarum Super cigarette in Bumiayu. The sampling method that used in this study is accidental sampling. The data is analyzed by using validity test, reliability test, classical assumption test, and multiple liniear regression test. The results show that the perceived price significantly influences the consumer buying interest of Djarum Super cigarette in Bumiayu, but the packaging and the attractiveness of television advertisement doesn’t significantly influences the consumer buying interest of Djarum Super cigarette in Bumiayu. Based on the R-squared, this research model just be able to explain 36% variant of consumer buying interest and 64% influenced by other variables that not investigated in this study.